تطبيق طريقة لعبة Make and Match لترقية مهارة القراءة لدى طالبات في المدرسة الدينية الوسطى بمعهد دار الفلاح الإسلامي الخامس جوكير جومبانج - Laila Kamila Hanum; Fathur Rohman (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
At Darul Falah 5 Islamic Boarding School in Jombang, many first-year students still struggle with reading Arabic texts and understanding their meanings accurately. Their enthusiasm for learning Arabic reading is low, largely due to traditional, non-interactive teaching methods that lead to passive learning. In response, the researcher conducted a qualitative case study titled "Applying the Make and Match Game Method to Improve Reading Skills among First-Year Students at Darul Falah 5 Islamic Boarding School in Jombang." Data was collected through observation, interviews, and documentation, and analyzed using data reduction, presentation, and conclusion drawing. The study found that the Make and Match method was effectively implemented by grouping students and using question-answer cards in matching activities. This fostered an interactive and enjoyable classroom environment. Despite challenges such as time constraints and varying participation levels, the method enhanced students' reading skills, especially in understanding Arabic texts and vocabulary. It also promoted student cooperation and aligned with cooperative learning theories. Overall, the Make and Match game significantly contributed to improving reading comprehension and language engagement among the students.